A Comparative Analysis of Tintern Abbey and Frost at Midnight from the Perspective of Ecocriticism - Ahmad, Jawad; Jian, Luo (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
This comparative analysis exploits the framework of ecocriticism to explore the themes of nature and the environment in William Wordsworth's "Tintern Abbey" and Samuel Taylor Coleridge's "Frost at Midnight." By examining the poetic techniques, imagery, and philosophical discourses employed by both poets, this article aims to shed light on how their respective works portray a deep connection and reverence for nature. The analysis delves into the shared themes of environmental consciousness, the spiritual significance of the natural world, and the role of memory in shaping one's relationship with the environment. Through a comparison of these two seminal Romantic poems, this study reveals the poets' nuanced perspectives on nature and offers insights into the broader ecological concerns of the Romantic period.